Induction of IL-10 and TGFβ from CD4+CD25+FoxP3+ T Cells Correlates with Parasite Load in Indian Kala-azar Patients Infected with Leishmania donovani. - Pradyot Bhattacharya; Smriti Ghosh; Sarfaraz Ahmad Ejazi; Mehebubar Rahaman; Krishna Pandey; Vidya Nand Ravi Das; Pradeep Das; Rama Prosad Goswami; Bibhuti Saha; Nahid Ali (Public Library of Science (PLoS), 2016)
BACKGROUND:Visceral leishmaniasis (VL) is distinguished by a complex interplay of immune response and parasite multiplication inside host cells. However, the direct association between different immunological correlates and parasite numbers remains largely unknown. METHODOLOGY/PRINCIPAL FINDINGS:We examined the plasma levels of different disease promoting/protective as well as Th17 cytokines and found IL-10, TGFβ and IL-17 to be significantly correlated with parasite load in VL patients (r = 0.52, 0.53 and 0.51 for IL-10, TGFβ and IL-17, respectively). We then extended our investigation to a more antigen-specific response and found leishmanial antigen stimulated levels of both IL-10 and TGFβ to be significantly associated with parasite load (r = 0.71 and 0.72 for IL-10 and TGFβ respectively). In addition to cytokines we also looked for different cellular subtypes that could contribute to cytokine secretion and parasite persistence. Our observations manifested an association between different Treg cell markers and disease progression as absolute numbers of CD4+CD25+ (r = 0.55), CD4+CD25hi (r = 0.61) as well as percentages of CD4+CD25+FoxP3+ T cells (r = 0.68) all correlated with parasite load. Encouraged by these results, we investigated a link between these immunological components and interestingly found both CD4+CD25+ and CD4+CD25+FoxP3+ Treg cells to secrete significantly (p<0.05) higher amounts of not only IL-10 but also TGFβ in comparison to corresponding CD25- T cells. CONCLUSIONS/SIGNIFICANCE:Our findings shed some light on source(s) of TGFβ and suggest an association between these disease promoting cytokines and Treg cells with parasite load during active disease. Moreover, the direct evidence of CD4+CD25+FoxP3+ Treg cells as a source of IL-10 and TGFβ during active VL could open new avenues for immunotherapy towards cure of this potentially fatal disease.